Altered Gut Microbiota Composition in Subjects Infected With Clonorchis sinensis - Xu, Meng; Jiang, Zhihua; Huang, Wen; Yin, Jianhai; Ou, Shen; Jiang, Yanyan; Meng, Liyu; Cao, Shengkui; Yu, Aiping; Cao, Jianping; Shen, Yujuan (Frontiers in Microbiology, 2018)
Clonorchiasis is an infectious disease caused by helminths of Clonorchis sinensis (C. sinensis). The adult parasite mainly inhabits the bile duct and gall bladder, and results in various complications to the hepatobiliary system. The amount of bile secreted into the intestine is reduced in cases of C. sinensis infection, which may alter the pH of the gut and decrease the amount of surfactant protein D, which was delivered to intestine via bile, in the human gut. However, the impact of parasites infection on the human gut microbiome remains unclear. To this end, we examined the gut microbiota composition in 47 modified Kato-Katz thick smear-positive (egg-positive) volunteers and 42 healthy controls from five rural communities. Subjects were grouped into four sub-populations based on age and infection status. High-throughput 16S rRNA gene sequencing revealed minimal changes in alpha diversity; however, there were alterations in the beta diversity between C. sinensis-infected subjects and healthy controls. In C. sinensis infected patients, we found the significantly reduction of anti-inflammatory taxa, such as Bacteroides and Bifidobacterium (P<0.05). Bacteroides, a predominant gut bacteria in healthy populations, was negatively correlated with C. sinensis eggs (EPG, r<0, P<0.05). And the reduction of abundance of Bifidobacterium, a common probiotic, was decreased particularly in the sub-population greater than 60 years old (r<0, P<0.05). The abundance of Dorea, a potentially pro-inflammatory microbe, was higher in infected subjects than in healthy individuals (P<0.05). Variovorax was a unique bacteria that was only detected in infected subjects. These results clearly demonstrate the significant influence of C. sinensis infection on the human gut microbiota and provided new insights into the control, prevention, diagnosis, and clinical study of clonorchiasis through the human gut microbiota.